Botanical Ecstasies: Psychoactive Plant Formulas in India and Beyond, by Matthew Clark. - Ferrari, Fabrizio (Religions of South Asia, 2022)
Botanical Ecstasies: Psychoactive Plant Formulas in India and Beyond, by Matthew Clark. London: Psychedelic Press, 2021. 69 pp. £9.99 (pb). ISBN 978191626711.